Bacillus velezensis Associated with Organomineral Fertilizer and Reduced Phosphate Doses Improves Soil Microbial—Chemical Properties and Biomass of Sugarcane - Santos, Hariane Luiz [UNESP]; Silva, Gustavo Ferreira da [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; Oliveira, Laura Costa; Nogueira, Carlos Henrique de Castro; Silva, Marcelo de Almeida [UNESP] (MDPI, 2022)
Appropriately using phosphorus (P) for the fertilization of sugarcane is critical to achieving high productivity because it is one of the most limiting nutrients in agricultural cropping systems. Thus, the objective of this research was to evaluate the morphological, biochemical, and yield responses of sugarcane, and the soil microbial–chemical properties, under the use of organomineral fertilizer (OF) associated or not with Bacillus velezensis strain UFV 3918 (B) combined with mono ammonium phosphate (MAP) doses. The experimental design used was completely randomized, consisting of eight treatments [Control (3/3 MAP); OF (without MAP); OF + 1/3 MAP; OF + 2/3 MAP; OF + 3/3 MAP; B + OF + 1/3 MAP; B + OF + 2/3 MAP; B + OF + 3/3 MAP] and four replicates. B + OF + 1/3 MAP provided increases in accumulated soil basal respiration (11.9%), carbon of microbial biomass (35.9%), fluorescein diacetate (12.7%), arylsulfatase (25.5%), and acid phosphatase (10.1%) activity compared to the control, which implied in higher shoot and total biomass. These results present a potential strategy for sugarcane fertilization, using bacteria in combination with OF to improve P nutrition and growth in sugarcane with reduced economic and environmental impact.
Keywords: Saccharum spp.; plant growth-promoting bacteria; soil microbial activity; soil enzyme activity; biomass production